Organizational Culture and Implications for Workplace Interventions to Reduce Sitting Time Among Office-Based Workers: A Systematic Review - Taylor, Wendell C.; Suminski, Richard R.; Das, Bhibha M.; Paxton, Raheem J.; Craig, Derek W. (Frontiers in Public Health, 2018)
Time spent in sedentary behaviors is an independent risk factor for several chronic diseases (e.g., cardiometabolic diseases, obesity, type 2 diabetes, and hypertension). Recently, interventions to reduce sitting time at work (a prominent sedentary behavior) have been developed and tested. Workplace culture plays a critical role in the success of interventions targeting sitting time in the workplace. However, there are a limited number of studies that have examined the role of work-place culture in reducing sitting time in the workplace. Therefore, in this review, we summarized the empirical literature investigating workplace culture and sedentary behavior and identify gaps in the knowledge base. Then, we present the rationale as to why there is a need to include the study of workplace culture in the context of interventions to reduce sedentary behavior. Furthermore, to advance the field of workplace health promotion, organizational culture, and interventions to reduce sitting at work, we present eleven recommendations. Our conclusion is that organizational culture is a critical component for the effectiveness of workplace initiatives.